2022
DOI: 10.1177/20539517221113774
|View full text |Cite
|
Sign up to set email alerts
|

Addressing ethical gaps in ‘Technology for Good’: Foregrounding care and capabilities

Abstract: This paper identifies and addresses persistent gaps in the consideration of ethical practice in ‘technology for good’ development contexts. Its main contribution is to model an integrative approach using multiple ethical frameworks to analyse and understand the everyday nature of ethical practice, including in professional practice among ‘technology for good’ start-ups. The paper identifies inherent paradoxes in the ‘technology for good’ sector as well as ethical gaps related to (1) the sometimes-misplaced ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Narrowing in on the technological and innovation aspect of global and sustainable development for the purposes of this Introduction, a discernible starting point at the intersection of PIT and global development are fields such as humanitarian engineering [19], [20], Tech for Good [21], [22], Civic Tech [23], [24] and Information Technology for Development (ICT4D, see the following section for further detail), among others. Other adjacent fields include responsible innovation [25], [26], [27], [28], socio-technical design / co-design / participatory design [29], [30], [31], [32], [33], [34], [35], and citizen science [8], [36], [37], [38].…”
Section: A Adjacent Fields and Conceptsmentioning
confidence: 99%
“…Narrowing in on the technological and innovation aspect of global and sustainable development for the purposes of this Introduction, a discernible starting point at the intersection of PIT and global development are fields such as humanitarian engineering [19], [20], Tech for Good [21], [22], Civic Tech [23], [24] and Information Technology for Development (ICT4D, see the following section for further detail), among others. Other adjacent fields include responsible innovation [25], [26], [27], [28], socio-technical design / co-design / participatory design [29], [30], [31], [32], [33], [34], [35], and citizen science [8], [36], [37], [38].…”
Section: A Adjacent Fields and Conceptsmentioning
confidence: 99%
“…With an increasing focus on ethics, it should then not come as a surprise that Data and AI for Good initiatives are often framed as outlets to confront ethical challenges; they can act as an outward expression of the willingness to face criticism and to show that data science can be ethical and work for good causes despite its shortcomings. Nevertheless, as Powell et al (2022) have shown for entrepreneurial Tech for Good networks, explicit pursuit of ethical practice and normative ideals can include paradoxes and practices that directly contradict the stated goals. The growing understanding of the data science profession may thus force us to consider the normatively prescriptive studies of what goodness ought to be not as external commentary but as debate that is internal to the data science profession itself.…”
Section: Ways Forward For Researchmentioning
confidence: 99%
“…Specifically, the paper expands on initial critical analyses by Madianou (2021), Magalhães and Couldry (2021) and Holzmeyer (2021). It also connects to the critical appraisal of ethical thinking in technology start-ups that follow the slogan 'Tech for Good' (Powell et al, 2022). These works offered critical readings of individual projects or programs but did not attempt to bring together a broader picture of Data and AI for Good as a family of initiatives, which is the goal of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…These tendencies align under the guise of infrastructural development via big tech capital, who inherit the one-worldism and violent universality of colonial development tendencies enacted by private sector forces. But drawing on media scholars Powell et al’s (2022) useful assertion, if “the ‘good’ in ‘technology for good’ continues to mask the structural issues inherent in our societies that cause the problems that need to be fixed through technology” (p. 3), we need more “context-centered” approaches to counter this universalism. While data and access to it can be useful and redirected towards less harmful ends, the current administrations, software, and infrastructures by which it is collected, analyzed, and utilized are resolutely in the hands of states and corporations, from software to hardware.…”
Section: Data Colonialism's Infrastructural Reachmentioning
confidence: 99%